PERCENTAGE OF BASOPHILS, EOSINOPHILS, AND NEUTROPHILS IN BALI CATTLE BLOOD BASED ON ORGANIC FEED - Santika, Putu Ayu; Suwiti, Ni Ketut; Setiasih, Ni Luh Eka (Buletin Veteriner Udayana, 2022)
One of the Bali cattle breeding maintenance is organic-based feeding. Organic-based feed is likely to not be as optimal as the composition of feed like feed in general, such as minerals and other organic substances. The condition and composition of the feed can affect the number of blood leukocytes and cause changes in the percentage of leukocyte cells such as basophils, eosinophils and neutrophils. This study aims to determine the percentage of basophils, eosinophils, neutrophils in bali cattle blood based on organic feed. This study was carried out on a farm owned by residents of the Village of Bulian, Kubutambah District, Buleleng Regency. Samples in the form of blood taken from 10 female bali cattle by vein using venoject. Next, blood smear preparations were made and then fixed and stained by Harris Hematoxillin-Eosin (HE). Percentage of basophils, eosinophils, neutrophils calculated by cross-sectional method. Data obtained and analyzed with descriptive quantitative. The results showed that cattle raised with an organic based maintenance system experienced basophilia, eosinophilia, and neutropenia.